A Focus Group Study of Retirement-Age Nurses: Balancing Tension and a Love of Nursing in a Changing Healthcare Environment. (December 2022) - Slusser, Kim; Knobf, M. Tish; Linsky, Sarah; Kaisen, Ann; Parkosewich, Janet; Sterne, Priscilla; Johnson, Cynthia; Carley, Jacqueline; Beckman, Beth
Abstract : OBJECTIVE: The aims of this study were to explore the experience of retirement-age nurses and identify decision-making factors and innovations to enhance retention. BACKGROUND: A national shortage of nurses has created challenges to preserving quality patient care and level of nursing competency and managing turnover costs. METHODS: A qualitative study using focus groups was conducted of nurses 55 years or older who were working or recently retired. Data were audiotaped and transcribed verbatim, with content analysis used to code in an iterative process until consensus was reached. RESULTS: The tension of balancing the love of patient care within a changing healthcare system was described. Patient acuity, competing roles, and the centrality of computers were stressors and integrally related. Flexibility in work schedules and new practice models were important to retirement decision making for work-life balance and retention. CONCLUSION: Passion for patient care dominated decisions to continue working. Innovations in practice models and scheduling offer opportunities to enhance the retention of experienced nurses.